ULTRASOUND FINDINGS OF BREAST MASSES WITH HISTOPATHOLOGICAL CORRELATION: A PROSPECTIVE STUDY. - Ranjan, Pushpa; Kumar, Dr . Vinod; Suman, Dr . Sanjay Kumar; singh, Dr . Anju (Student’s Journal of Health Research Africa, 2024)
Background Breast carcinoma is the most frequent cancer and cause of death in women worldwide and in India. Early breast cancer diagnosis and therapy reduce mortality. Breast lesions are first imaged using ultrasound due of its availability, radiation-free nature, and good cost-benefit ratio. Ultrasound is preferred over mammography for diagnosing breast lesions in thick breasts and during pregnancy and lactation. Aim To differentiate breast lesions into benign and malignant lesions. Correlate benign and malignant lesions with histopathological findings. Methodology This was a prospective study. 100 patients were evaluated by ultrasound and lesions were categorized according to the Breast Imaging Reporting and Data System, Sonographic findings were correlated with histopathological findings, and statistical analysis was done. Results The age distribution of the patients ranged from 15 to 75 years, with a mean age of approximately 45 years. The study found that 68% of the patients had benign lesions and 32% had malignant lesions according to ultrasound. Histopathological examination confirmed that 63 patients had benign lesions, while 37 had malignant lesions. There were 2 false-positive cases (radial scars) and 5 false-negative cases (malignant phyllodes, metastatic lesions, and papillary carcinoma). The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of ultrasound in diagnosing breast lesions were found to be 85.7%, 96.9%, 93.7%, 92.6%, and 93%, respectively. The most common benign lesions were fibroadenomas, followed by fibrocystic disease. Among malignant lesions, infiltrative ductal carcinoma was the most common. Conclusions Results demonstrated a positive correlation between the sonographic findings and histopathological diagnoses of the breast masses. Recommendation Ultrasound should be utilized as a primary imaging modality for evaluating breast lesions, particularly in resource-limited settings and for patients with dense breast tissue, to facilitate early and accurate differentiation between benign and malignant lesions, thereby improving patient management and outcomes.